Nutritional composition of pear fruits ( PYRUS COMMUNIS). - M.U, Mahammad; A. S, Kamba; L, Abubakar; E.A, Bagna (Global Journal of Food and Agribusiness Management, 2011)
Nutritive and anti-nutritive composition of pears fruit (PYRUS COMMUNIS) were evaluated using standard method in, 2010. The objective of the study is to investigate the nutritional properties of pear fruit. The results analysis shows that the moisture content of seed, pulp and peel were 52.3± 1.15, 78.0± 0.57 and 64.2± 075% respectively and ash content for the seed and pulp are 2.20 ± 0.40 and 5.34± 0.57%, while that of peel had 1.60 ± 0.35% . The crude protein content is 26.00 ± 0.0% seed, pulp 14.38 ± 0.07%, while peel contains the least protein content 9.45± 0.26. The crude lipid and fibre were also found in significant amount in all the samples. The available carbohydrate content of seed, pulp is 98.21 ± 3.54%, 89.08 ± 2.02% while peel has 96.01± 00. Calculated energy values were in the range of: seed > peel > pulp. The results of mineral analysis indicated that both the samples contained appreciable amount of mineral elements with potassium as the predominant element in the samples. Amino acid composition Glutamic has highest values in both the seed and pulp 11.73, 6.58 followed by Aspartic with 8.56 seed and 5.79 for pulp while Methionine is the least 1.05 in the seed and Tyrosine with 0.34 in the peel.Antinutritional analysis showed that HCN, nitrate, oxalate, phytate were lower than the reference toxic standards. Therefore, the seed, pulp and peel of pear have potential nutritional uses.